The Importance of Blood Is Infinite: Conceptions of Blood as Life Force, Rumours and Fear of Trial Participation in a Fulani Village in Rural Gambia. - Sarah O'Neill; Susan Dierickx; Joseph Okebe; Edgard Dabira; Charlotte Gryseels; Umberto d'Alessandro; Koen Peeters Grietens (PLoS ONE)
Background Clinical trials require high levels of participation and low drop-out rates to be successful. However, collecting blood samples from individuals recruited into clinical trials can be challenging when there is reticence about blood-taking. In addition to concerns regarding the feasibility of medical research, fears of 'blood-stealing' and 'blood-selling' have ethical implications related to cultural sensitivity and informed consent. This study explores anxieties around blood-taking during a malaria treatment trial in the Gambia. Methods This case study is based on ethnographic research in one theoretically selected village due to the high reticence to screening for the clinical trial 'Primaquine's gametocytocidal efficacy in malaria asymptomatic carriers treated with dihydroartemisinin-piperaquine' carried out in the Gambia between 2013 and 2014. Data collection tools included in-depth interviews, participant observation, informal conversations and group discussions. Results In total only 176 of 411 habitants (42%) in the village accepted having a bloodspot taken to screen for malaria. Although trial recruitment was initially high in the village, some families refused screening when rumours started spreading that the trial team was taking too much blood. Concerns about 'loss of blood' were equated to loss of strength and lack of good food to replenish bodily forces. Families in the study village were concerned about the weakness of their body while they had to harvest their crops at the time of recruitment for the trial. Conclusion A common recommendation to prevent and avoid rumours against public health interventions and trials is the provision of full and consistent information during the consent procedure, which is assumed to lead to more accurate knowledge of the purpose of the intervention and increased trial participation. However, even when information provision is continuous, the emergence of rumours can be related to times of uncertainty and perceptions of vulnerability, which are often a reflection of structural inequalities and diverging value orientations between communities and public health institutions.